FREQUENCY OF PREMALIGNANT LESIONS IN WOMEN SCREENED BY PAP SMEAR - Khan, Ahmad Ahsan; Nayyar, Shazia (Pakistan Journal of Physiology, 2018)
Background: Cervical cancer related morbidity and mortality among women are major health problems in developing countries. Premalignant lesion of the cervix, i.e., intraepithelial neoplasia precedes cervical cancer and can be detected by Pap smear test. This study aimed to determine the prevalence of premalignant lesion of cervix in District Quetta. Methods: This study was based on 100 cases from the Outpatient Department of Obstetrics and Gynaecology at Combined Military Hospital Quetta. The selection criterion was sexually active patients presenting with complaints of vaginal discharge, dyspareunia, menorrhagia and lower abdominal pain. Patients less than 20 years of age, known cases of intraepithelial or invasive malignancy, and natives outside District Quetta were excluded. After fixation and staining, each smear was carefully examined according to criteria laid down by The Bethesda System for reporting cervical cytology. Results: Mean age of the patients was 47 years. The presenting complaints in descending order of frequency included lower abdominal pain 39%, vaginal discharge 29%, menorrhagia 28% and post coital bleeding in 4%. Out of 100 cases, 17 (17%) cases were positive for premalignant lesions and 79 (79%) were negative, whereas 4 (4%) were inadequate for analysis. Conclusion: Pre-malignant lesions of the cervix are common in District Quetta and can be diagnosed early by Pap smears.